Computed tomographic appearance of circumcaval and circumuterine ureter in a cat - Jitrapun Jirasakul; Ninlawan Thammasiri; Damri Darawiroj; Nan Choisunirachon; Chutimon Thanaboonnipat (Veterinary Medicine and Science, 2020)
Abstract Background Circumcaval ureter is a rare congenital anomaly resulting from the persistence of embryonic venous system. This anomaly is characterized by running of affected ureter around caudal vena cava (CVC). Case presentation In this report, circumcaval ureter was found in a 2‐year‐old female cat attending as normal sample group in another research. This cat passed all health checkup protocols before computed tomography (CT) was performed. Conclusion The contrast‐enhanced computed tomographic (cCT) images clearly revealed the dislocation of the right ureter that course around CVC and uterine body. This is the first report of feline circumcaval concurrent with circumuterine ureter detected by cCT.